Synthesis, electrochemical, structural and theoretical study of new derivatives of O-B-N and O-B-O heterocycles - Mikysek, Tomáš; Kvapilová, Hana; Doušová, Hana; Josefík, František; Šimůnek, Petr; Růžičková, Zdeňka; Ludvík, Jiří (My University, 2017)
Three new oxazaborine and two boron diketonate derivatives containing different structural motifs were synthesized and studied using NMR, electrochemistry (CV, RDV, and dc-polarography), UV–Vis spectra and X-ray structure analysis. The experimental data were correlated with quantum chemical calculations. The main attention was focused on determination of the first oxidation and the first reduction potentials, their relationship to the calculated HOMO and LUMO energies and to their UV–Vis spectra. The electro- chemical data reflect the structure–redox properties relationship depending on location of oxidation and reduction center.
Syntéza, elektrochemická, strukturní a teoretická studie nově syntetizovaných derivátů O-B-N a O-B-O heterocyklů
Keywords: boron heterocycles; synthesis; Electrochemistry; HOMO-LUMO; DFT calculations; Syntéza; heterocykly bóru; elektrochemie; HOMO-LUMO; DFT kalkulace